Spruce xylan/HEMA-SBA15 hybrid hydrogels as a potential scaffold for fibroblast growth and attachment. (1st December 2018) - García-Uriostegui, L.; Delgado, E.; Meléndez-Ortiz, H. Iván; Camacho-Villegas, T.A.; Esquivel-Solís, H.; Gatenholm, P.; Toriz, G.
Highlights: Acryloylated xylan acted as co-macromer/crosslinker in hybrid pHEMA/SBA15 hydrogels. Spruce xylan/pHEMA hydrogels support the growth of fibroblast. SBA15 particles (20% wt.) enhanced two-fold the mechanical properties of hydrogels. Fibroblasts spread better on the hybrid hydrogel. Abstract: A hybrid hydrogel (GHC-SBA15) based on spruce xylan (HC), 2-hydroxyethyl methacrylate (HEMA), and mesoporous silica (SBA15) was prepared with the intended use of fibroblast attachment and growth. Xylan was functionalized with acryloyl chloride to introduce vinyl groups and was crosslinked by radical polymerization with HEMA in presence of SBA15. Infrared spectroscopy and nuclear magnetic resonance confirmed the copolymerization of HEMA with xylan. Up to 20 wt.% addition, SBA15 was homogenously incorporated in the structured hydrogel network as observed by SEM. Moreover, nitrogen adsorption–desorption, small angle X-ray scattering and transmission electron microscopy indicated that the mesoporous SBA15 framework was maintained and that the hybrid hydrogel was a physical mixture of SBA15 with the copolymer HC/HEMA. Rheological analysis revealed that addition of 20% w/w SBA15 into hydrogel enhanced significantly the mechanical properties. In addition, we demonstrate that fibroblast L929 cells grew and spread on GHC-SBA15. Cell viability was within the expected range.